Implementasi Metode Keteladanan Guru dalam Pembentukan Kepedulian Sosial Siswa - Ahmad Sahiba; Hj. Zainap Hartati (ISLAMIKA, 2022)
Education as the most important need of students is through school, because most of the students are in school. Therefore, schools have an important role for the development of student education, including attitudes and character. Social care is one of the characters that need to be instilled in students. The task of a teacher to provide character education is very important. Exemplary methods in Islamic education are considered effective for increasing students' social awareness. Therefore, the author carried out a study to find out how the teacher's exemplary rules for fostering a sense of concern for his students. Using descriptive qualitative methods. The results of the study show that the teacher's exemplary rules for student social care are impressive. The teacher may set an example for students through etiquette that can be imitated, charity that can be imitated and help that can be imitated.